2015
DOI: 10.1021/cn500272a
|View full text |Cite
|
Sign up to set email alerts
|

A Cyclic Peptide Mimic of the β-Amyloid Binding Domain on Transthyretin

Abstract: Self-association of β-amyloid (Aβ) into oligomers and fibrils is associated with Alzheimer’s disease (AD), motivating the search for compounds that bind to and inhibit Aβ oligomerization and/or neurotoxicity. Peptides are an attractive class of such compounds, with potential advantages over small molecules in affinity and specificity. Self-complementation and peptide library screening are two strategies that have been employed in the search for peptides that bind to Aβ. Alternatively, one could design Aβ-bindi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(50 citation statements)
references
References 39 publications
2
46
0
2
Order By: Relevance
“…[14] In this work we used human iPSC-derived neurons to detect cellular Aβ binding as a function of aggregation state, and to determine if cG8 and/or mTTR altered the cellular binding and internalization of Aβ. To do this, cells were treated with Aβ monomer, oligomer, or fibrils prepared alone or with cG8 or mTTR.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[14] In this work we used human iPSC-derived neurons to detect cellular Aβ binding as a function of aggregation state, and to determine if cG8 and/or mTTR altered the cellular binding and internalization of Aβ. To do this, cells were treated with Aβ monomer, oligomer, or fibrils prepared alone or with cG8 or mTTR.…”
Section: Resultsmentioning
confidence: 99%
“…As described previously, our data are consistent with the hypothesis that binding of mTTR to oligomers completely arrests both the adoption of extended cross-β conformation and further self-assembly· [11d] The mechanism of action of cyclic peptides is similar, except that cyclic peptides also re-directs the self-association of a fraction of Aβ into large non-fibrillar amorphous clusters. [14] Although both mTTR and cG8 potently inhibit fibrillogenesis of Aβ, neither disaggregates preformed Aβ fibrils (Figure 4C,D). This is a favorable feature of an anti-Aβ compound if intermediate oligomeric aggregates are indeed the most toxic species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cyclized 22-mer, CG3, proved to be more effective than the linear peptide at suppressing A β aggregation into fibrils, and at protecting neurons against A β toxicity (Figure 1). 35 …”
mentioning
confidence: 99%
“…TTR suppressed Aβ and prevent its toxicity [89] [90]. Studies showed that TTR sequestered Aβ in the CSF and J. Iqbal Journal of Behavioral and Brain Science moved Aβ to the choroid plexus (CP) for enzymatic degradation and removal from the brain [18].…”
Section: Ttr Role In Alzheimer Diseasementioning
confidence: 99%